Pra-Studi Analisis Paparan Konsentrasi PM2,5 dan CO2 di dalam Rumah: Preliminary Study Analysis of Exposure to PM2.5 and CO2 Concentrations in the House - Indra Chandra; Sherly Liana Putri; Rahmat Awaludin Salam; Lulu Millatina Rachmawati; Nabil Ananta Hasmul; Muhammad Fajri Hadi Syahputra (BRIN Publishing (Penerbit BRIN), 2023)
In this COVID-19 pandemic period, the majority of people do their activities indoors. A high number of activities could increase indoor pollution. Some of the pollutants easily found in the house include particulate matter with sizes of <2.5 micrometers (PM2.5) and carbon dioxide (CO2). Both types of these pollutants can enter the body and interfere with health. This study aims to measure the concentration of pollutants in the house and estimate daily exposure and risk level. This study measured the concentration of PM2.5 and CO2 in two houses, house A located in a housing complex in Bandung Regency, and house B, located on the side of Garut City main road. The measuring instruments are placed in 3 points: kitchen, family room, and outdoors. The concentration of PM2.5 in the neighborhood of house A is higher than the concentration of PM2.5 in the neighborhood of house B due to the high construction activity. Large ventilation in house A causes the PM2.5 concentration to follow the outdoor concentration pattern. As for house B, the concentration of PM2.5 is much influenced by the source from the kitchen. The activities much influence the concentration of CO2 for both houses in each room. The relative risk of PM2.5 for cardiovascular and cardiopulmonary disease in each house differed depending on the duration of exposure. Calculation of the relative risk of PM2.5 was conducted on normal people in house A and house B, and the chef in house B. The highest relative risk was obtained by the chef in house B, followed by normal people in house B and house A. The level of relative risk for the chef at house B is 30% for cardiovascular disease and 34% for cardiopulmonary disease. ABSTRAK Di masa pandemi COVID-19, mayoritas masyarakat melakukan kegiatannya di dalam rumah. Aktivitas yang tinggi dapat menyebabkan polutan dalam rumah meningkat. Beberapa jenis polutan dapat dengan mudah ditemukan di dalam rumah di antaranya adalah partikulat berukuran <2,5 mikrometer (PM2,5) dan karbon dioksida (CO2). Kedua jenis polutan tersebut dapat masuk ke dalam tubuh dan mengganggu kesehatan. Penelitian ini bertujuan untuk mengukur konsentrasi polutan dalam rumah dan mengestimasi paparan harian dan tingkat risikonya. Penelitian ini mengukur konsentrasi PM2,5 dan CO2 di dua tipe rumah, yaitu rumah A yang terletak di perumahan Kota Bandung, dan rumah B, terletak di samping jalan utama kota Garut. Alat ukur diletakan pada tiga ruangan, yaitu dapur, ruang keluarga, dan luar ruang. Lingkungan rumah A memiliki konsentrasi polutan PM2,5 yang lebih tinggi dari rumah B karena tingginya aktivitas pembangunan permukiman dan jalur kereta cepat. Ventilasi yang besar pada rumah A menyebabkan konsentrasi PM2,5 cenderung mengikuti pola luar ruang. Sementara itu untuk rumah B, tingginya aktivitas di dapur mempengaruhi konsentrasi polutan PM2,5 dalam rumah. Konsentrasi CO2 untuk kedua rumah pun berbeda untuk tiap ruang. Rata-rata sumber CO2 pada tiap ruang di masing-masing dipengaruhi oleh aktivitas dari tiap ruangan tersebut. Tingkat risiko PM2,5 terhadap penyakit kardiovaskular dan kardiopulmoner pada masing-masing rumah berbeda tergantung dari durasi paparannya. Perhitungan tingkat risiko PM2,5 dilakukan pada orang normal di rumah A dan B, dan juru masak di rumah B. Tingkat risiko tertinggi dihasilkan oleh juru masak di rumah B, diikuti dengan orang normal di rumah B dan A. Tingkat risiko pada juru masak di rumah B sebesar 30% untuk penyakit kardiovaskular dan 34% untuk penyakit kardiopulmoner.